Recent Advances in Follicular Variant of Papillary Thyroid Carcinoma - Chen, MD, Haiying; Izevbaye, MD, PhD, Iyare; Chen, MD, Frank; Weinstein, MD, Barbara (North American Journal of Medicine and Science, 2012)
The follicular variant of papillary thyroid carcinoma (FVPTC) constitutes a distinct class of papillary thyroid carcinoma (PTC), presenting unique challenges to the clinician and pathologist regarding its diagnosis, prognosis and treatment. Fifty years since its identification as a unique class of thyroid neoplasms, controversies still exist with respect to the histologic diagnosis and categorization of FVPTC. While agreement exists among experts as to its generic place within PTC, FVPTC exhibits biologic and molecular properties that distinguish it from conventional PTC. Many studies and proposals utilizing histopathologic criteria, immunohistochemical and molecular techniques have been brought to bear on the problems posed by these set of tumors with varying degrees of success. Here we examine the clinical and pathologic features of FVPTC, highlighting diagnostic controversies and recent molecular findings that attempt to provide clues to the proper classification of this unique group of thyroid tumors. [N A J Med Sci. 2012;5(4):212-216.]